"Comparative analysis by total yield, antimicrobial and phytochemical evaluation of curcuminoid of district Kasur: With its potential use and characterization in electrospinning nanofibers". (30th June 2022) - Charan, Tanzeel Rehman; Bhutto, Muhammad Aqeel; Bhutto, Mihr Ali; Tunio, Azhar Ali; Murtaza, Ghulam; Aftab, Umair; Kandhro, Farhartullah; Khaskheli, Sheeraz Ahmed
It has been reported through various studies that turmeric of different geographical regions has variabilities regarding the number of phytochemicals, some have a better curcuminoid yield, some have better antimicrobial and antioxidant activities, and even turmeric of some regions does not show compatibility with modern applications due to having unfavorable quality. So, here in this study, we have tried to demonstrate the potential and efficacy of locally produced turmeric powder from district Kasur, Pakistan, through a comparative study with turmeric powder of international grade, analyzing their activity against pathogenic micro-organisms, presence of the number of phytochemicals, and presence of curcuminoid compounds like curcumin, extracted in four different solvents (ethanol, methanol, acetone and chloroform), and were verified by TLC and FTIR spectroscopy. This study justifies that the locally produced turmeric has better quality and potential as it gives a maximum curcuminoid yield of about 25% in Ethanol solvent and showed maximum zone of inhibition against E.coli about 14mm and 16mm against Staphylococcus aureus. While Antifungal activity was also observed high; as compared to the same amount of does of international grade turmeric extract. Further, electrospun nanofibers successfully generated from curcuminoid of Kasur Pakistan with PVA, present uniform, smooth nanofibers with an average diameter of 227. 49 nm. Finally, this study suggests that turmeric of Kasur has similar or more potential as compared to turmeric of international grade, and can be used/replaced in nanotechnology labs for various applications.